Impact of condom balloon tamponade on the rate of obstetric hysterectomy: a ten-year study - Roy, Archana; Mishra, Nalini; Sai, Mamta; Pal, Sanjita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this present study was to assess the efficacy of condom uterine balloon tamponade (C-UBT) in averting the obstetric hysterectomy (OH) in cases of major postpartum haemorrhage (PPH) over a period of 10 years. Methods: A retrospective cohort study from January 2010 to December 2019. A historical cohort was drawn from a group of women who had OH for major PPH between Jan 2010 to December 2014 (Group 1) whereas those from January 2015 to December 2019 were designated as Group 2. Total 305 C-UBT were used in the later period. Women who had OH at <28 weeks were excluded from the study. Primary outcome was to determine the efficacy of C-UBT in averting the risk of OH. Secondary objective was to determine the success rate of C-UBT after five years of use Results: Total 37463 births occurred from January 2010 to December 2014 and 38808 during January 2015 to December 2019. Cases of OH were 33 in the first five years period (Group 1) and 20 in the later (Group 2), p=<05, odds ratio=0.58 with 95% CI 0.335-1.019 favoring C-UBT. After exclusion of rupture uterus and placenta accreta syndrome, OH for uterine atony alone were 22 (66.6%) for Group 1 and 08 (40%) for Group 2, P=0.01 odds ratio=0.350 (95% CI 0.156-0.788). No OH was done in group 2 for placenta previa. Efficacy of C-UBT was 96%. Conclusions: C-UBT is very safe, cheap and effective option for averting OH and associated physical, emotional and psychosocial morbidity.